An Analysis of Juridical Determination of Market Value Fees for Acquisition of Inheritance Type Land and Building Rights by Regional Revenue Agency of Malang City - Sandi Permana Nugraha; Tunggul Anshari Setia Negara; Dyah Widhiawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The state has the power to collect taxes from its citizens. Article 23 A of the 1945 Constitution of the Republic of Indonesia is the constitutional basis for tax collection by the government, namely the